PENGEMBANGAN INSTRUMEN LITERASI DIGITAL SEKOLAH, SISWA DAN GURU - Asyti Febliza; Oktariani Okatariani (Jurnal Pendidikan Kimia Universitas Riau, 2020)
This study aims to develop digital literacy instruments for schools, teachers and students whose function is to measure the extent of the digital literacy levels of schools, teachers, and students. It is not possible for a school to follow the development of science and technology if the school's potential is inadequate and its human resources are not ready. Therefore, the development of digital literacy instruments needs to be made in order to identify the level of readiness of schools, teachers and students in facing the digital era in the industrial revolution 4.0. Subjects of the study were 90 respondents consisting of 30 teachers and 60 students in SMA Negeri 14 Pekanbaru. The questionnaire that was made was first validated by 2 expert validators, after being declared valid by the expert validator, then the questionnaire was conducted a limited test to calculate the level of validity and reliability of each question item. The questionnaire uses a Likert scale with 3 categories of answer choices (often, rarely, never or there is, is being planned, no, etc.). Based on the results and conclusions, conclusions can be drawn, namely: the items that can be used as data collection tools on the school digital literacy questionnaire instrument are 23 questions, while the items that can be used as data collection tools on the teacher's digital literacy questionnaire are 52 items and instrument digital student literacy questionnaire as many as 31 questions. Based on the reliability criteria, the three digital literacy questionnaires show high and very high reliability criteria with a reliability level greater than 0.684.